Digestibility and nutritional value of dried and whole acorn flour in ovines - Boza, J.; Fonollá, J.; Varela, G. (Ars Pharmaceutica (Internet), 1966)
The coefficients of digestibility and nutritive value of the non-decorticated and dried acorn flour, using the difference method, in a diet formed by acorn flour and dehydrated alfalfa flour, have been obtained experimentally in Manchego ovids. , previously obtaining in the same animals the digestibility coefficients of the alfalfa flour used. The experiments have been carried out following the standards given by the European Zootechnics Federation, and a battery of four metabolism cells in the Experimental Station of El Zaidín, in Granada.